Monografia jest konieczna. Monografia jest niemożliwa - Kudyba, Wojciech (Colloquia Litteraria, 2011)
Monography is indispensable. Monography is impossible It is difficult to imagine the history of literature devoid of such mode of research expression as monography. It is still a popular form of synthetic expressions (after all the history of literature is condemned to synthesis). At the same time, however, a literary historian can base his actions less and less often on the theoretical-literary reflection. What vectors could turn us today towards a contemporary reading of literary texts – the reading which is far not only from ingenuous naivety but also from dangerous confidence in the power of individual research concepts? Some contemporary postulates of reading ethics give answer to these questions. They induce us to be distant towards any theoretical-literary or ideological prejudices and hence to the responsibility for the research method and the language describing a work of art. It seems that a thought which returns in the reflection of literary studies about the subjectivity of reading, about the necessity of considering the sphere of values in the process of reading (which modern ethics of reading calls for) induces to turn towards interpretation, return to the author and to axiology.